Environmental variability during the Last Interglacial: a new high‐resolution pollen record from Tenaghi Philippon, Greece. (13th February 2013) - Milner, Alice M.; Müller, Ulrich C.; Roucoux, Katherine H.; Collier, Richard E. L.; Pross, Jörg; Kalaitzidis, Stavros; Christanis, Kimon; Tzedakis, Polychronis C.
Abstract A new high‐resolution Last Interglacial pollen record from the Tenaghi Philippon peatland, northeast Greece, documents variability in forest composition and cover, which we attribute to changes in temperature and moisture availability. The declining stage of the interglacial was marked by a stepwise decrease in temperate tree populations and culminated in the complete collapse of forest at the onset of the ensuing stadial. The coincidence of the onset of the stepwise declining trend with the increased prominence of North Atlantic ice‐rafting events suggests that ecological thresholds in southern Europe were only crossed once ice rafting events intensified, and implies that changes in North Atlantic ocean circulation were an important contributing factor to the declining temperate forest cover in southern Europe. Our results provide evidence for intra‐interglacial variability in the low mid latitudes and suggest a coupling between the high northern latitudes and the northeast Mediterranean during this interval. Copyright © 2013 John Wiley & Sons, Ltd.